Immune Profiling in Asymptomatic Atlantic Salmon (Salmo Salar L.) Naturally Infected with Orthoreovirus Piscis-1 (Prv-1) - Sandino-Garcia, A; Maisey-Munoz, K; Reyes-Lopez, F; Vallejos-Vidal, E; Santillan-Araneda, M; Imarai-Bahamonde, C (Academic Press, 2026)
Orthoreovirus piscis-1 (PRV-1), the causative agent of heart and skeletal muscle inflammation (HSMI) in Atlantic salmon (Salmo salar), is a prevalent pathogen in salmonid aquaculture worldwide. In Chile, PRV-1 is highly prevalent, with over 80 % positivity in farming centers. However, HSMI outbreaks are infrequent, and associated mortality rates remain low. While PRV-1 immunology has been studied extensively in laboratory settings, the immune responses of naturally infected and phenotypically asymptomatic fish in field conditions are poorly understood. Therefore, this study investigated the immune responses of asymptomatic fish naturally infected with PRV-1 by analyzing leukocyte distributions in the blood and immune transcriptomic profiles in two lymphoid organs (head kidney; spleen). A robust Th1-mediated immune response was observed in the spleen, with significant upregulation of cd4-1, tbet, ifn-γ, and il12. Conversely, the head kidney exhibited minimal transcript regulation, consistent with its roles in hematopoiesis and innate immunity. Interestingly, IgM transcript levels did not differ significantly between PRV-positive and PRV-negative fish in both organs, suggesting that PRV-1 persistence is not solely driven by humoral immune evasion. These findings emphasize the organ-specific nature of PRV-1 immune responses, with the spleen playing a pivotal role in adaptive Th1-mediated immunity during asymptomatic infections. Understanding these immune mechanisms provides critical insights into PRV-1 persistence and its interaction with the host immune system, offering valuable information for developing improved management strategies in salmon aquaculture. © 2025
Keywords: Asymptomatic infection; Cell-mediated immunity; Lymphocytes; Th1 immune response; Orthoreovirus piscis-1 (PRV-1); Atlantic salmon; Aquaculture